(untitled) (Al-Qamar, 2024)
Malaysia has firmly established itself as a global leader in Islamic finance, positioning the country as a key destination for foreign investment in Shariah-compliant financial products and services. Over the years, the country’s strategic combination of well-developed legal and regulatory frameworks, government incentives, and specialized infrastructure has made it an attractive hub for both domestic and international investors. Malaysia’s Islamic finance market, encompassing products such as Islamic banking, sukuk (Islamic bonds), takaful (Islamic insurance), and Shariah-compliant equity investments, has seen remarkable growth. However, despite the country’s significant advancements, foreign investors continue to face a number of challenges. These include regulatory complexity, bureaucratic hurdles, and legal risks in cross-border transactions, particularly in navigating the diverse interpretations of Shariah law and ensuring compliance with local and international legal standards. This paper examines the opportunities and challenges facing foreign investors in Malaysia’s Islamic finance sector, offering a comprehensive analysis of the country’s Islamic finance ecosystem, regulatory environment, and government initiatives. The paper also proposes policy recommendations aimed at enhancing Malaysia’s appeal to global investors, focusing on streamlining regulatory processes, harmonizing Shariah interpretations, and expanding the range of Shariah-compliant financial products.